SYEKH MUSTHOFA HUSEIN DAN POLITIK PENDIDIKAN ISLAM: ANALISIS DAMPAK TERHADAP PERKEMBANGAN PENDIDIKAN ISLAM DI TAPANULI SELATAN - Lidia Kusmira; Zainal Efendi Hsb (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
This study aims to examine the role and contributions of Syekh Musthofa Husein in Islamic education politics and its impact on the development of Islamic education in South Tapanuli. Syekh Musthofa Husein is known as a prominent Islamic scholar who was actively involved not only in religious matters but also in advancing Islamic education through social and political channels. This research uses a qualitative-descriptive approach through literature review and in-depth interviews with key figures and educational institutions influenced by his efforts. The findings reveal that Syekh Musthofa Husein's political approach to Islamic education included the establishment of pesantren-based educational institutions, the strengthening of Islamic curriculum, and advocacy for education policies rooted in Islamic values. His influence is significant, as seen in the growth of Islamic educational institutions in South Tapanuli, increased community participation in religious education, and the emergence of a generation of Muslim intellectuals grounded in local traditions and Islamic teachings. This study highlights the crucial role of Islamic scholars in shaping contextual and sustainable Islamic education policies.